Prevalence of smear positive pulmonary tuberculosis among prisoners in North Gondar Zone Prison, northwest Ethiopia - Moges Beyene; Amare Bemnet; Asfaw Fanaye; Tesfaye Wogahta; Tiruneh Moges; Belyhun Yeshambel; Mulu Andargachew; Kassu Afework (BMC Infectious Diseases, 2012)
Abstract Background People concentrated in congregated systems, such as prisons, are important but often neglected reservoirs for TB transmission, and threaten those in the outside community. Therefore, this study was conducted to determine the prevalence of tuberculosis in a prison system of North Gondar Zone. Methods An active case-finding survey in North Gondar Prison was carried out from March to May 2011. All prison inmates who had history of cough for at least a week were included in the study. Three morning sputum samples were collected from suspected inmates and examined through fluorescence microscopy. Fine needle aspiration cytology was done for those having significant lymphadenopathy. Pre and post HIV test counseling was provided after written consent. Binary logistic and multivariable analysis was performed using SPSS version 16. Results A total of 250 prisoners were included in the survey. Among these, 26 (10.4%) prisoners were found to have TB giving a point prevalence of 1482.3 per 100,000 populations of smear positive TB among the TB suspects. All the inmates who participated in the study volunteered for HIV testing and a total of 19(7.6%) inmates were found to be reactive for the HIV antibody test amongst of which 9(47.4%) had TB co-infection. The prevalence of HIV infection in the TB infected inmates was found to be 34.6% (9/26). From the 26 TB cases identified 12 (46.2%) were having under nutrition (BMI < 18.5kg/m2). Conclusions There is high prevalence of TB in North Gondar Prison with possible active transmission of TB within the prison. There was a high prevalence of HIV among the TB suspects. Strong cooperation between prison authorities and the national tuberculosis control programmes is urgently required to develop locally appropriate interventions to reduce transmission. The determinants for poor nutrition in the prison need also further investigation.